Fire Ceramic Sculpture in the Context of Contemporary Ukrainian Art: Art and Technology - Zinenko, Tetiana; Zinenko, Alisa; Chopenko, Nina; Muravlov, Volodymyr (International Journal of Engineering and Technology, 2018)
This article explores the phenomenon of fiery ceramic sculpture as a part of contemporary art culture, also here researches projection of this phenomenon into Ukrainian realityInformation includes data about this genre of art, its history, theoretical and terminological aspects. The article analyzes and systematizes artistic achievements of Ukrainian artists Andrei Sobyanin, Vyacheslav Vinkovsky, Alexander Shehanin, Vyacheslav Gudenok. Additionally, the paper explores the experience of introducing the author's ceramic sculpture at the symposiums in Opishne, Gaspra, Nikopol (Ukraine) and Daugavpils (Latvia).Â Â